Izbrani vidiki družbenega prostora kot podlaga za razumevanje "modernizacije" visokošolskega izobraževanja - Pavlin, Samo (Družboslovne razprave, 2018)
Based on selected aspects of the social space, we establish a conceptual model for developing indicators of the modernisation of higher education systems. The described dynamic relates to the issue of understanding the social fluidity and sustainability of higher education systems with respect to the labour market. This can be observed on both the individual and system levels. Our conceptual model is based on learning spaces and their physical design, the transfer of learning to employers, the role of virtual space in learning, student mobility and motility and the theoretical assumptions made by Lefebvre and Foucault. In the article, we demonstrate that exploring selected socio-spatial aspects of higher education offers a vital perspective for understanding changes in higher education's contemporary role on the national and European levels.
Keywords: Družbena mobilnost; družbeni prostor; Higher education; Labor market; Modernisation; Modernizacija; Prostor; Social mobility; Space; Trg dela; Visoko šolstvo